2008
DOI: 10.1007/s00285-008-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

Signaling cascades as cellular devices for spatial computations

Abstract: Signaling networks usually include protein-modification cycles. Cascades of such cycles are the backbones of multiple signaling pathways. Protein gradients emerge from the spatial separation of opposing enzymes, such as kinases and phosphatases, or guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs) for GTPase cycles. We show that different diffusivities of an active protein form and an inactive form leads to spatial gradients of protein abundance in the cytoplasm. For a cascade of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…Among the numerous examples of cascades are proteolytic cascades in blood clotting, phoshorylation cascades in intracellular signal transduction systems, and gene expression cascades that control cell differentiation. Biophysical studies of lumped cascades have shown that they can serve as noise filters, time-delay, or thresholding elements, but the operation and functional capabilities of spatially distributed cascades are much less understood (1)(2)(3)(4)(5)(6). One class of problems where this understanding is necessary arises in studies of embryonic pattern formation.…”
mentioning
confidence: 99%
“…Among the numerous examples of cascades are proteolytic cascades in blood clotting, phoshorylation cascades in intracellular signal transduction systems, and gene expression cascades that control cell differentiation. Biophysical studies of lumped cascades have shown that they can serve as noise filters, time-delay, or thresholding elements, but the operation and functional capabilities of spatially distributed cascades are much less understood (1)(2)(3)(4)(5)(6). One class of problems where this understanding is necessary arises in studies of embryonic pattern formation.…”
mentioning
confidence: 99%
“…Although mechanics and chemistry are individually sufficient to give rise to structure at micrometer-length scales, increasing evidence suggests that the joint contribution of both of them leads to novel phenomena that might be important for subcellular organization: The interactions of diffusible molecules with the cytoskeleton can alter their mobility and localization, greatly modifying reaction-diffusion processes (4)(5)(6)(7)(8); large-scale patterns can arise if signaling molecules are advected by the motors they regulate (9) or if they recruit factors that further activate them (10); and a shallow reaction-diffusion signaling gradient can produce a sharp concentration gradient in a downstream factor if the signaling molecule regulates the cooperative association of the downstream factor (11). Thus, there is a plethora of mechanisms capable of generating subcellular organization from mechanics, chemistry, or a combination of the two, but it is unclear how prevalent these different possibilities are in cells.…”
mentioning
confidence: 99%
“…7, the reaction-diffusion equations that govern the spatiotemporal dynamics of active GTPase fractions, g 1 p(x,t), g 2 p(x,t) and g 3 p(x,t), are presented as follows (see Eqs. 8 and 9), 6 …”
Section: Spatiotemporal Dynamics Of Active Gtpase Fractions In a Thrementioning
confidence: 99%
“…This spatial heterogeneity facilitates the generation of positional information 21,22 . Even if a GTPase cascade displays only a single, stable steady state, the spatial segregation of GEFs and opposing GAPs on different cellular structures can result in complex spatial patterns of GTPase activities 6,[23][24][25] . Such complex activity profiles were observed for a chromosome-dependent RanGTPase-importin cascade 26,27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation